Vulnerability Prediction of Medicinal Plants Used by Karen People in Chiang Mai Province to Climatic Change Using Species Distribution Model (SDM) - Kornkanok Tangjitman (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This study aims to investigate the knowledge of traditional medicinal plants of the Karen people in Chiang Mai Province. It also aims to evaluate the potential impact of climate change and the vulnerability of these medicinal plant species. The data on the medicinal plants were gathered from previous ethno-botanical studies that focused on the Karen people of Chiang Mai Province and through study field trips. In total, 379 medicinal plant species in 271 genera and 117 families were documented from 14 Karen villages in Chiang Mai Province. The cultural importance (CI) index was also applied in order to identify the important medicinal plants of the Karen people. It was shown that most of the medicinal plants demonstrated different CI values from the different Karen villages. The potential impact of climate change was evaluated on 244 wild plants species using species distribution models (SDM). Climatic and non-climatic variables were used to develop the distribution models. The greenhouse gas emissions scenarios, A1B (medium-high emissions) and A2 (high emissions) of the Hadley Centre Coupled Model, along with version 3 (HadCM3) were used to examine the potential future species distribution under climatic changes for the years 2050 and 2080. It was found that a combination of climatic and non-climatic factors would result in substantial effects on the distribution of these medicinal plant species. It is predicted that more than 60% of the plants were predicted to suffer significant losses in their suitable ranges by the years 2050 and 2080, respectively. Moreover, increased turnover rates of the plant species were also indicated. Following the International Union for Conservation of Nature and Natural Resources (IUCN) Red List criteria, one (Lycopodium cernuum) and four (Lilium primulinum, Lycopodium cernuum, Schima wallichii and Vitex trifolia) species were predicted to become extinct due to climate change in Chiang Mai Province under A1B or A2 scenarios by the years 2050 and 2080, respectively. Moreover, a total 171 plant species were predicted to lose their suitable ranges and were categorized as being critically endangered (51 species), endangered (44 species), vulnerable (25 species) and near threatened (51 species), respectively, whereas 73 species were predicted to gain more ranges or to see no change in their areas and were categorized as being of least concern under A1B or A2 scenarios by the year 2080. Raising the climate change awareness of the Karen people and supporting concepts of the sustainable use of medicinal plants will be crucial in preserving the medicinal plants of the Karen people. Scientists and government authorities are recommended to help with in-situ conservation strategies in protected areas by preserving suitable habitats with proper management and control plans. However, ex-situ conservation strategies may also be needed to reduce the negative impacts of climate change on these medicinal plants.